Anti-CD20 Treatment of Autoimmune Hemolytic Anemia Refractory to Corticosteroids and Azathioprine: A Pediatric Case Report and Mini Review - Alexandros Makis; Zoi Kanta; Dimitrios Kalogeropoulos; Nikoloaos Chaliasos (Case Reports in Hematology)
Autoimmune hemolytic anemia (AIHA) is a relatively uncommon hematological entity in children and sometimes is characterized by a severe course requiring more than one line course therapy. Treatment decisions depend on the severity and chronicity of the anemia and the characteristics of the autoantibodies. Immunosuppression with corticosteroids is the first-line treatment, especially in warm-reactive AIHA. Refractory cases are treated with immunosuppressive drugs, cytotoxic agents, androgens, or splenectomy, with various side effects and questionable efficacy. Another second-line option is rituximab, an anti-CD20 monoclonal antibody, which has been used as an off-label agent with encouraging results from small limited studies or case reports. Herein, we add our experience on the safety and clinical efficacy of rituximab by presenting the case of a boy with warm-type AIHA resistant to corticosteroids and azathioprine, successfully treated with rituximab. We also offer a review of the relevant literature.